Niedojrzałość emocjonalna w powiązaniu z uzależnieniem od alkoholu i gier hazardowych jako przyczyna niezdolności konsensualnej w świetle wyroku c. Monier z dnia 21 listopada 2018 roku - Wieczorek, Michał (Ius Matrimoniale, 2018)
According to the canon law there are different causes of inability to contract a marriage. However in practice it is difficult to distinguish one specific cause of a psychic nature. In the Monier’s sentence, immaturity is linked to the addiction to alcohol and gambling. According to the judges, the man was afflicted with a serious disorganisation of the personality. In consequence, this premise became the basis for the ascertainment of marriage invalidity. It should be emphasised that emotional immaturity in this case was not the primary and exclusive problem of the person. Therefore, the reasoning of the Rotal Court in Monier’s judgement shows that the whole life history of the person in question should be taken into account while deciding about consensual disability.